Different dimensions of conspicuous consumption in the emerging market of Bangladesh - Moutusi Tanha; Ather Yeasir Fahim; Shahira Tasnim; Md Ali Reza Raju; Waliul Islam; Fahimuzzaman Shawn; Moin Talukder; Md. Jahidul Islam (goodwood publishing, 2022)
Purpose: This study wishes to explore the level of understanding of how consumers in the market perceive conspicuous consumption. Research methodology: A qualitative research process was applied for collecting and evaluating the information, and the data is collected using the Ethnographic and Netnographic approaches to conduct this study. Results: Customers buy luxury things based on aesthetic value, originality, social standing, desired states, and money use. For social standing, people purchase premium products. The desire to consume luxury items and services also encourage their conspicuous purchase, according to the research. People use luxury things to maximize their fortune. Limitations: This research is conducted within Bangladesh. If it is broader research and there is available time, the study can be performed in different regions of the country. Core data can be obtained if observing each respondent for a long time is possible. Contribution: According to this study, Bangladeshi consumers redefine luxury through their product attitudes. This research has managerial and academic uses. This research teaches about conspicuous consumption. This study suggests luxury brand owners modify items to diverse countries so cultural differences don't affect conspicuous purchasing. As counterfeit items may be dangerous to health, particularly electronics, marketing managers can raise awareness by researching this research.